Contribution of artificial intelligence (AI) to construction project management processes: State of the art with scoping review method - Aladag, Hande; Guven, Ilkim; Balli, Osman (YILDIZ TECHNICAL UNIV, 2024)
The Artificial Intelligence (AI) is being considered as a new way to tackle the challenges frequently faced by the Architecture, Engineering and Construction (AEC) industry in terms of its ability to leverage advanced technologies, data analysis techniques, and automation to address specific challenges and improve efficiency, productivity, safety, decision-making, and overall project outcomes. Thus, it is imperative to know the future of AI in construction project management processes. With this background, this study aims to detect application areas of AI in construction project management processes by using scoping review method and create a base for the development of theories that can support future studies. According to the findings of studies, application areas of AI in project management domain are generally clustered under eight main topics: cost, time, quality, contract, dispute, risk, safety, and sustainability. In line with the findings, this study contributes in two-folds. As the theoretical contribution researchers can benefit from this study, which addresses the research trends and current applications of this ground-breaking technology in project management processes, by mapping the current interest in AI studies. The future studies can be directed in line with identified gaps and justifications. As the practical contributions, construction companies that want to be the early movers can benefit from the findings of this study as they reveal crucial areas where they can focus their investment on areas where AI can make the most significant difference to address their company's specific requirements.
Keywords: Artificial Intelligence (AI); Construction Industry; Construction Management; Project Management; Scoping Review; Engineering